An Empirical Comparison of Stochastic Dominance among Lognormal Prospects - Tehranian, Hassan; Helms, Billy P. (Journal of Financial and Quantitative Analysis, 1982)
Hassan Tehranian, Billy P. Helms, An Empirical Comparison of Stochastic Dominance among Lognormal Prospects, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 2 (Jun., 1982), pp. 217-226